Basella rubra and Bryophyllum: a promising treatment for stone(pathari) disease - T, Khelker; M, Agrawal; S, Tiwari (Journal of Phytology, 2012)
The Bastar and another southern district of Chhattisgarh state is famous for Kulthi, Harnwa whose botanical name is Basella rubra and belongs to family Papilionatae/Papilionoideae. The soil texture of this region is very suitable for cultivation of kulthi and harnwa. The farmers of this area have been cultivating this crop for food from decades ago. The local knowledgeable people use Kulthi pods and other parts of plant for treatment of Pathari or stone disease. The medical science says that the responsible factors for this disease are the accumulation of calcium oxalate in gall balder, kidney or uterus etc. Symptoms of this disease are seen mainly on these parts of body which ultimately result in loss of appetite and patient may even become anemic. The treatment of this disease by allopathic way is to dissolve the calcium oxalate by various drugs.